Beneath the bending skies : [large type] a novel - Kirkpatrick, Jane, 1946- (Center Point Large Print, 2022)
"Mollie Sheehan has spent much of her life striving to be a dutiful daughter and honor her father's wishes, even when doing so has led to one heartbreak after another. After all, what options does she truly have in 1860s Montana? But providing for her stepfamily during her father's long absences doesn't keep her from wishing for more. When romance blooms between her and Peter Ronan, Mollie finally allows herself to hope for a brighter future -- until her father voices his disapproval of the match and moves her to California to ensure the breakup. Still, time and providence are at work, even when circumstances are at their bleakest. Mollie may soon find that someone far greater than her father is in control of the course of her life -- and that even the command to "honor thy father" has its limits. Beneath the Bending Skies is a sweeping story of hospitality, destiny, and the bonds of family"--